Who understands and how? – exploring nurses’ perceptions of the readability and usability of instructions written by hospital pharmacists - Henri Satokangas; Kirsi Kvarnström; Hanna M. Tolonen (BMC Health Services Research)
Abstract Background Clear and precise instructions are essential for high-quality medication management. This study focuses on identifying usability and functionality of instructional materials on medicine handling and use produced by hospital pharmacists. The secondary aim is to provide recommendations for hospital pharmacists on writing instructional texts. Methods Semi-structured interviews were conducted with nurses who read and used medication-related instructions written by hospital pharmacists in a large tertiary hospital in Finland. Data were analyzed using inductive content analysis, incorporating an applied linguistic analysis of the grammatical and structural features of the Finnish-language instructional texts. The analysis focused on the nurses’ instruction-reading practices, identifying both problems and well-functioning dimensions of the texts, and proposing improvements for this type of communication between healthcare professionals. Results The interviewed nurses (n = 9) consistently found the instructions somewhat challenging, primarily due to their length, complex structure and limited accessibility. While the interviewees stated that the instructions did not present personal difficulties, they expressed concern that other staff in the ward might struggle with the instructions. According to the interviews, readability problems can be mitigated using visual support. Linguistic features such as terminology and the interpretation of impersonal grammatical structures (e.g., passive voice) related to the division of labor were not seen as problematic for the interviewees. The usability of the instructions was enhanced by effective communication with the hospital pharmacists. Conclusion When producing instructions for staff on the wards, it is important to focus on both internal text features, such as the use of graphics and consistent terminology, as well as external factors, like easy access communication between hospital pharmacists and ward staff.